Factor Associated with Mortality of Hospitalized Cancer Patients with COVID-19 Infection in Indonesia National Cancer Center - Kurniawati, Sri Agustini; Sutandyo, Noorwati; Tadjoedin, Hilman; Pradipta, Jaka; Ismuha, Ratu Ralna; Ummah, Citra Dovina Khaira; Suryana, Kresna Dharma; Budi, Erwin (Indonesian Journal of Cancer, 2024)
Background: Cancer patients with COVID-19 are at risk of developing severe complications and outcomes due to immunosuppressive and inflammatory states. This study aims to provide insight into risk factors associated with mortality in this population. Methods: A retrospective cohort study was conducted at Dharmais National Cancer Center, Jakarta, Indonesia, from May 2020 to July 2021. Data were collected through electronic medical records using the consecutive sampling technique. The numerical and categorical data were then tested statistically. Results: The results showed 180 cancer patients with COVID-19 were hospitalized at Dharmais National Cancer Center. Among the patients, 114 patients survived, and 66 patients deceased. Across all risk factors analyzed to mortality, patients with Diabetes Mellitus (OR 0.41;0.22-0.77, p-value 0.05) and high level of D-dimer (OR 2.00;1.06-3.79, P-value 0.05) have a higher risk in mortality. The Results showed that survived patients have lower D-dimer levels (2010 ng/L) and deceased patients have higher D-dimer levels (3264 ng/L) with P-value 0.05. Conclusion: High D-dimer levels and diabetes are risk factors significantly associated with mortality in hospitalized cancer patients with COVID-19 Infection.